2010
DOI: 10.1111/j.1365-2486.2009.02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of organic surface horizons of boreal soils into warmer regions alters microbiology but not the temperature sensitivity of decomposition

Abstract: Pekka Vanhala, Kristiina Karhu, Mikko Tuomi, Katarina Bjorklof, Hannu Fritze, Hasse Hyvarinen, & Jari Liski, 'Transplantation of organic surface horizons of boreal soils into warmer regions alters microbiology but not the temperature sensitiviy of decomposition', Global Change Biology, Vol. 17 (1): 538-550, first published 16 December 2009. The version of record is available online at doi: 10.1111/j.1365-2486.2009.02154.x ?? 2010 Blackwell Publishing LtdChanges in soil carbon, the largest terrestrial carbon po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 63 publications
5
47
0
Order By: Relevance
“…The use of soil transplant as a proxy to study the effects of global changes has been successfully demonstrated in both plant biology and microbiology (Balser and Firestone, 2005;Breeuwer et al, 2010;De Frenne et al, 2011;Lazzaro et al, 2011;Vanhala et al, 2011). It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012).…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…The use of soil transplant as a proxy to study the effects of global changes has been successfully demonstrated in both plant biology and microbiology (Balser and Firestone, 2005;Breeuwer et al, 2010;De Frenne et al, 2011;Lazzaro et al, 2011;Vanhala et al, 2011). It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012).…”
Section: Introductionsupporting
confidence: 72%
“…It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012). Nevertheless, it remains unclear how microbial functional potentials, representing the underlying mechanisms of microbial community metabolism, are altered.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Methodologically, questions pertaining to the relative impacts of climate and soil can be most powerfully addressed through studies of reciprocal soil transplantation, whereby different types of soils are reciprocally transferred to different climate regions and subjected to parallel testing over a short or long period of time (28)(29)(30). To this end, we performed the first large-scale soil transplantation experiment under open field conditions.…”
mentioning
confidence: 99%